The (in)visibility of deafness: Identity, stigma, quality of life and the potential role of totally implantable cochlear implants - Chi Yhun Lo; Robyn Clay‐Williams; Beth Elks; Chris Warren; Frances Rapport (Health Expectations)
Abstract Introduction The disclosure of deafness is complex, given the historic and on‐going stigma associated with being deaf. The aim of this study was to explore how identity, stigma, and quality of life may be impacted when using cochlear implants (CIs) and totally implantable cochlear implants (TICIs). The physical difference between these two assistive listening devices is significant, given many CI users opt to hide their sound processor behind hair or headwear, in contrast to TICIs (an emerging technology) whereby all components are implanted internally and thus invisible. Methods This qualitative study involved semistructured interviews and demographic questionnaires with 12 adult participants with more than 1 year of experience using their CI. Participants were recruited Australia‐wide through community organisations that support deaf and hard‐of‐hearing individuals. Interview transcripts were analysed thematically, with the themes generated through an inductive process, with consensus generated through group working with three members from the research team. Results Four major themes were identified: (1) CI challenges; (2) The importance of social and support networks; (3) Identity and disclosure and (4) Concerns about TICIs. The underlying finding was centred around the construction of deaf identity. Participant attitudes were generally categorised as ‘Loud and proud’, with the recognition that displaying the CI was an extension of self, something to be proud of, and a means to normalise deafness; or ‘Out of sight and out of mind’, which sought to minimise the visibility of deafness. While both identities differed in how deafness is disclosed, they are fundamentally related to the same ideas of self‐agency and empowerment. Conclusion TICIs present a novel opportunity—the ability for CI users to control the visibility of their deafness and thus control disclosure. This study explored the impact of stigma and categorised two core identities that CI users construct. Future directions include investigating potential CI candidates, to explore if TICIs may be a facilitator to CI uptake. Patient or Public Contribution The semistructured interview guide was developed in consultation with adults with CIs. Feedback led to adjustments and improvement to the interview guide. In addition, F. R. has a lived experience with hearing loss, and C. Y. L. is an executive committee member for a nonprofit charity organisation that supports families that are D/deaf and hard‐of‐hearing.